The privacy concerns in location based services: protection approaches and remaining challenges - Basiri, Anahid; Moore, Terry; Hill, Chris (2016)
Despite the growth in the developments of the Location Based Services (LBS) applications, there are still several challenges remaining. One of the most important concerns about LBS, shared by many users and service providers is the privacy. Privacy has been considered as a big threat to the adoption of LBS among many users and consequently to the growth of LBS markets. This paper discusses the privacy concerns associated with location data, and the current privacy protection approaches. It reviews the advantages and disadvantages of each approach and evaluates the effectiveness of the available solutions. In order to detection of the remaining challenges (including the gaps between users demand and what the available solution can offer, a survey is conducted. This helps to estimates the importance and required protection level of the location privacy for different LBS applications. The results of the survey shows the public view on privacy concerns has changed over last years, this may be because of the wider popularity of social media and location based social networking services. Although there are technical, social regulatory policies to protect location privacy, there are still big challenges remaining, including misunderstanding about the privacy threats due to the lack of mutual understanding between users and LBS providers (including developers, policy makers and researchers).